AN ANALYSIS OF STUDENTS’ ABILITY TO COMPREHEND RECOUNT TEXT AT THE TENTH GRADE SMA NEGERI 2 TANJUNGPINANG - English Education FKIP (Universitas Maritim Raja Ali Haji, 2020)
The objective of this research was to know students’ ability to comprehend recount text at the tenth-grade students of SMAN 2 Tanjungpinang. This research was a descriptive quantitative method. In this research, the researcher used one class as a sample that is X MIA 6. The researcher used random sampling and done by lottery. The instrument used in this research was a test in the form of multiple-choice with 25 questions and 7 recount text. In analysis data, the researcher used the Rasch model and winsteps application version 3.73. According to Mahfoodh (2007), there are five aspects of reading comprehension. They are: identifying the main idea, finding specific information, making a conclusion, determining reference, and understanding vocabulary. In this research, standard deviation of students’ comprehension to get the main idea 1.11 logit included in excellent category, standard deviation of students’ comprehension to find specific information 1.88 logit included in excellent category, standard deviation of students’ comprehension to get a conclusion 0.68 logit included in good category, standard deviation of students’ comprehension of determining reference 0.00 logit included in good category, and standard deviation of students’ vocabulary 1.19 logit included in good category. Based on the result of the research, students’ ability to comprehend recount text included in the good category. It can be seen from the value of standard deviation 1.01 logit. The categories of students’ ability adapted from Sumintono and Widhiarso (2015): excellent: > 1.33 logit, good: -1.33 – 1.33 logit, poor: < -1.33 logit.